2020
DOI: 10.1186/s13287-020-01784-7
|View full text |Cite
|
Sign up to set email alerts
|

hUMSC transplantation restores ovarian function in POI rats by inhibiting autophagy of theca-interstitial cells via the AMPK/mTOR signaling pathway

Abstract: Background: Previous studies of primary ovarian insufficiency (POI) have focused on granulosa cells (GCs) and ignored the role of theca-interstitial cells (TICs). This study aims to explore the mechanism of the protective effects of human umbilical cord-derived mesenchymal stem cells (hUMSCs) on ovarian function in POI rats by regulating autophagy of TICs. Methods: The POI model was established in rats treated with cisplatin (CDDP). The hUMSCs were transplanted into POI rats by tail vein. Enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…According to reports in the literature, CDDP as a common anticancer drug can lead to POI [12,24]. The POI model was generated by daily intraperitoneal injections of CDDP (2 mg/kg, dissolved in saline) for 7 days [25,26]. The rats were randomly assigned to four groups: control, POI + hUMSCs, POI, and POI + PBS group.…”
Section: Group and Treatmentmentioning
confidence: 99%
“…According to reports in the literature, CDDP as a common anticancer drug can lead to POI [12,24]. The POI model was generated by daily intraperitoneal injections of CDDP (2 mg/kg, dissolved in saline) for 7 days [25,26]. The rats were randomly assigned to four groups: control, POI + hUMSCs, POI, and POI + PBS group.…”
Section: Group and Treatmentmentioning
confidence: 99%
“…Many studies have demonstrated that TSCs are recruited and differentiated into TCs, forming the follicular membranes surrounding the GCs to provide structural support and contribute to steroidogenesis for follicle maturation 21 , 47 . Lu et al reported that human umbilical cord-derived mesenchymal stem cell transplantation can restore the ovarian function by alleviating theca-interstitial cells apoptosis in POI rats 48 . We hypothesized that TSCs were more suitable for POI therapy as tissue resident stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yin et al (2020) demonstrated that heme oxygenase-1 (HO-1) gene overexpress in hUCMSCs mediated restoration of the ovarian reserve of POI mice by regulating autophagy through the JNK/Bcl-2 signaling pathway. In addition, hUCMSCs restored ovarian function in POI rats by regulating ROS levels through the autophagy-related AMPK/mTOR pathway ( Lu et al, 2020 ). Huang et al (2019) showed that fetal liver MSCs exerted antioxidant effects by lowering ROS levels to restore ovary function in POI models.…”
Section: Mechanism Of Mscs-based Treatment For Poimentioning
confidence: 99%